Here comes the boom - Coraci, Frank; Garner, Todd.; Loeb, Allan; James, Kevin, 1965-; Hayek, Salma, 1966-; Winkler, Henry, 1945-; Germann, Greg.; Rogan, Joe, 1967-; Rutten, Bas, 1965-; Columbia Pictures; Happy Madison (Firm); Broken Road Productions; et al. (Culver City, Calif. : Sony Pictures Home Entertainment, 2013)
High school biology teacher Scott Voss is desperate to save the music program at his cash-strapped school. Learning that fighting in MMA matches provides a pretty nice payout, Voss decides to put his former collegiate wrestling skills to the test and climb into the octagon. Unfortunately, Voss has been out of college for about 20 years. Does he have what it takes to beat the best and earn the cash the school desperately needs?
Special features: Deleted scenes; gag-reel; cast featurette.
Originally released as a motion picture in 2012.
Kevin James, Joe Rogan, Greg Germann, Salma Hayek, Henry Winkler, Bas Rutten.
MPAA rating: PG; for bouts of MMA sport violence, some rude humor and language.
DVD; NTSC, region 1; widescreen (1.85:1); Dolby Digital 5.1.
English, French, Spanish or Thai dialogue, with optional Spanish, French, Mandarin, Thai, Korean, Cantonese or English subtitles; English SDH.
Keywords: High school teachers -- Drama; Fund raising -- Drama; Wrestlers -- Drama; Mixed Martial Arts -- United States -- Drama; Comedy films; Feature films; Video recordings for the hearing impaired